Numerical study of combustion characteristics and emission in diesel engine using LPG-hydrogen-diesel fuel mixture - Abd Al-Reda, Radhwan Ali (2017)
Towards the effort of reducing pollutant emissions, especially nitrogen oxides, and smoke, from diesel engine direct injection (DI), engineers have proposed various solutions; one of these solutions is the use of alternative gaseous fuel. Using alternative gasses fuels like liquefied petroleum gas (LPG), hydrogen (H2), etc., for the modified diesel engine are receiving more interest from many scientists due to many reasons including the national concerns of the liquid fuels limited resources, the environment advantage and the needs to use a reliable, durable, and efficient engine. However, diesel-H2 and diesel-LPG dual fuel engine produced many of the unwanted effects such as rapid burning rate, increase diffusivity, and high emission levels. Therefore, researchers started focusing on tri-fuel engines. Hence, LPG addition to the diesel-H2 operation has the ability to make hydrogen combustion smoother and stable which can prevent imperfect combustion, such as the sharp increase of peak in-cylinder pressure and temperature also lowers the combustion temperature of hydrogen in order to repress Nitrogen Oxides (NOx) emission. As a result, better performance engine can be obtained when H2 is added with LPG to make a secondary fuel for diesel dual fuel engine. In the present study, the usage of ANSYS design modular was chosen to create the entire computational domain of the engine and for Computational Fluid Dynamic (CFD) the FLUENT approach was used for Ricardo Hydra diesel engine, a single cylinder engine that operates using the direct injection method. A two-dimensional CFD code was used in the study in order to examine the emissions and combustion characteristics of a diesel engine, diesel-LPG, diesel-H2 under dual-fuel, and diesel- LPG-H2 under tri-fuel operations, with different air-fuel ratios (λ) such as 1.2, 1.6, 2, and 2.4. In addition, in order to choose the best reduction towards the emission, evaluate the best manner of fuel gasses under dual and tri-fuel conditions was conducted. Moreover, torque (20.18 Nm), intake temperature (298 K), and engine speed (2000 rpm) were taken constantly to an atmospheric condition. The effects of a number of the cells on the expected result were utilized in order to analyze the most accurate one. The simulation data of in-cylinder pressure and verification of Nitrogen Oxides (NOx) emission appears to achieve a good agreement with data from previous work. The results obvious the successfully established a CFD simulation was obtained for predicting the emissions and combustion characteristics on the diesel, dual, and tri-fuel engine operations. Knowledge of utilizing the dual and tri-fuel in modify diesel engine and understanding the acceptable values of the mixture to give the best results. The addition of gasses fuels increases the peak temperature under all values of excess air. However, the addition of gaseous fuel only increased the in-cylinder pressure for excess air values of 1.2, 1.6, and 2. On the other hand, at 2.4 excess air, the peak pressure increased through the increase of the limit value of H2, such as 60L-40H and 50L-50H, when added to LPG. A decrease is then observed with diesel-H2 modes. This might be a result of the low amount of fuels in the air when compared to other similar cases and lean burn operation engine. At dual fuel operations, adding H2 decreases CO and CO2 emissions when compared with the emission from LPG. Conversely, diesel-LPG-H2 tri-fuel operations lowered the CO emission when compared to diesel-LPG. It also lowered Nitrogen Oxides (NOx) emission when compared to the diesel-H2 operation for all excess air. In order to lower CO/CO2 emissions, high H2 fraction is proposed in LPG (50L-50H). On the other hand, lower H2 fraction in LPG (90L-10H) can lower the uncontrolled combustion of hydrogen combustion and restrict the increase of Nitrogen Oxides (NOx) emission.